The Changes of Nutrient Content in Soil in Long-term Fertilizer Experiments (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper describes the influence of long term (more than 30 years) fertilizer application to the changes of soil properties and identifies the influence of different fertilization rates to phosphorus, potassium, calcium and magnesium accumulation in soil.The research has been carried out at the Research Institute of Agriculture of Latvian University of Agriculture in the long-term subsurface drainage field established in Skrīveri in 1981 under the guidance of professor J. Štikāns.  The long-term drainage field was established in the uncultivated gleyic sod-podzolic Hypostagnic Endogleyic Albeluvisol (Hypereutric), stw-ng-AB(he) loam that had not been used in agriculture for 20 years before. The experimental field was established with four rates of mineral fertilizers: without fertilizers, N45P30K45; N90P60K90 N135P90K135 calculated in form of P2O5 and K2O. Since 1994 a seven-year crop rotation has been organized: 1) winter triticale, 2) potatoes, 3) spring wheat, 4) spring oilseed rape, 5) spring barley + perennial grasses (red clover, timothy), 6) perennial grasses, 1st year of using, and 7) perennial grasses 2nd year of using. Mineral fertilizers were applied according to the anticipated rates of plant nutrient elements annually during the cultivation of soil before sowing. For winter cultivars the phosphorus as superphosphate and potassium as potassium chloride fertilizers were cultivated before the sowing in autumn and nitrogen in form of ammonium nitrate was applied the next spring at the beginning of vegetation and at the stage of tillering. During the vegetation period all the required common agro-technical measures were taken – treatment with herbicides, fungicides and insecticides.After 32 years of trial similar soil parameters showed significantly different content of nutrients related to the different level of fertilizer application. On a low background of fertilizers (N45P30K45) a small increase of mobile phosphorus in soil has only been observed in recent years. At the fertilizer rate N90P60K90 the content of available phosphorus and potassium in soil gradually begins to grow. Fertilization norm N135P90K135 caused a constant accumulation of nutrients in soil. In 30 years’ time the content of exchangeable phosphorus (calcium lactate – extractable) has increased more than 20 times (from 9 till 184 mg P2O5 kg-1) and exchangeable potassium (calcium lactate – extractable) has increased more than 4 times (from 64 till 223 mg K2O kg-1). There were no relation between different fertilizing rates and calcium and magnesium content in soil observed.